Influência da clorexidina na avaliação qualitativa e quantitativa da preservação da camada híbrida utilizando diferentes sistemas adesivos à dentina humana - Gonçalves Junior, Ubiratan (2016)
The dental materials have undergone important advances in recent decades, but the union interface dentin / adhesive is still a challenge for the restorative dentistry. The objective of this study was to evaluate the influence of chlorhexidine in preserving the hybrid layer using different adhesive systems to human dentin. They selected 60 third healthy human molars. The occlusal enamel was cut to dentin exposure. The specimens were initially divided into two groups (n = 30) according to treatment with chlorhexidine or not, as follows: control group (C) and group treated with chlorhexidine for 60 seconds after etching (CHX). Later, each group was divided into 3 subgroups (n = 10) according to the adhesive system used, as follows: Single Bond Universal (SBU), Amber (AMB) and Futurabond (FUT). All specimens were restored with composite resin Filtek Supreme XT (3M ESPE, St. Paul, USA) and cut into sticks with ± 1mm2 sectional area. Samples obtained from five teeth from each group were submitted for immediate analysis microtensile and five teeth were stored in artificial saliva and microtensile performed after 6 months of storage. The data were analyzed by factor analysis of variance (ANOVA 3-way) and Tukey's test (α = 0.05). Difference in bond strength values were detected among the adhesive systems, and the Single Bond Universal and Ambar had higher values. Samples stored in artificial saliva and tested after 6 months showed a reduction in bond strength values. Pretreatment of dentin with 2% chlorhexidine able to maintain the bond strength values for the SBU group. So chlorhexidine influence the bond strength values of an adhesive system tested, and there were differences between the tested adhesives.